From Rooftops to Futures Transforming Vocational Education Through Solar Power at SMKS Panca Budi - Juliangga, Reza; Irwanto, Muhammad (Blantika: Multidisciplinary Journal, 2025)
Rising electricity costs have become a pressing concern for schools across Indonesia, with prices climbing roughly 10% each year. SMKS Panca Budi in Medan faced this challenge head-on by embracing solar power technology. Through a collaborative program between Universitas Pembangunan Panca Budi and Universiti Malaysia Perlis, we introduced solar energy to the school community in February 2025. The initiative combined classroom presentations, hands-on workshops, and the installation of a 50 kW solar system on the school's rooftops. This system now supplies about one-third of the school's electricity needs. More importantly, students and teachers developed genuine understanding and enthusiasm for renewable energy. The workshops gave vocational students practical skills they can use in their future careers. What started as an energy-saving project evolved into a comprehensive learning experience that changed how the school community thinks about power, sustainability, and their role in Indonesia's energy future.